Effect Of Health Education On The Improvement Of Tuberculosis Patient Knowledge And Attitude About Infection Prevention In Health Simo Tuberculosis - Hesti Ummami, Yuwana, Abi Muhlisin, SKM, M.Kep (2016)
Tuberculosis (TB) is an infectious disease of the lungs caused by bacteria such as Mycobacterium tuberculosis. Indonesia ranks fourth in the world after China, Africa and India with 450,000 new cases, 64,000 deaths / year and 6,100 cases of Multi Drug Resistant TB (MDR) each year. Based on preliminary studies of the health center Simo obtained in 2015 there were 23 patients who showed positive TB. 2014 and obtained 18 with smear-positive . This study aims ntuk determine the effect of health education on the knowledge and attitude of tuberculosis patients in preventing transmission of pulmonary tuberculosis in Puskesmas Simo Boyolali. This research used experimental design pretest-posttest 0ne Test Group. Analysis resullt shows that there are significant health education on knowledge on the value of p = 0.000, there is the influence of health education on attitudes p = 0.000. Patient knowledge about the prevention of transmission of pulmonary tuberculosis in the clinic simo before health education have less knowledge means that they lack an understanding of the knowledge of prevention of transmission of tuberculosis. And after health education most knowledge of the patient to be good. Attitudes of patients on the prevention of transmission of tuberculosis before health education on tuberculosis before health education on tuberculosis average neutral and refused. After health education most people are supportive attitude.